MONITORING, EVALUATING AND FURTHERING THE COMMERCIAL USAGE OF TOURISM AND HOSPITALITY INDUSTRY RESEARCH PROJECTS IN 2018 - Kittinorarat, Jakkrapan; Paholpak, Jutathip; Naklungka, Kanlaya; Paholpak, Surapol (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2021)
This research project was supported by Thailand Science Research and Innovation (TSRI) to analyze, monitor, evaluate, and drive the utilization of the research output of 39 tourism and service industry research projects in the year 2018. It was found that most of the research programs had research output in line with the tourism development strategy and the national development strategy set by the government, and related agencies. The most prominent research program was 5.1% and the most prominent was 17.9%. Most of the research programs were evaluated at a good level and the research results were carried out in accordance with the action plans and objectives set. In addition, some of the research programs were models for advocating for commercial use. This research, therefore, provided recommendations for managing the fundraising process as well as presenting a model for driving research into useful applications for other research teams in research development following the various strategies of the country and the process of driving research output to commercial use in order to truly create value from research in the economy and society of the study area.